Pengaruh Perbedaan Suhu dan Waktu Pengeringan Terhadap Parameter Mutu Karagenan Dari Eucheuma spinosum - Andayani, Rina; Andhiarto, Yanu; Muslikh, Faisal Akhmal; Widjaja, Bambang; Della, Desi Mujiastuti; Farida, Agustini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Carrageenan is widely used in various industries, such as food and beverages, cosmetics, and pharmaceuticals, due to its important role as a viscosity regulator, stabilizer, thickener, developer, gelling agent, and excellent stabilizing agent. Temperature and drying duration are important factors that affect the quality of the final product. This study aims to examine the quality characteristics of carrageenan from Eucheuma spinosum dried using the oven method, considering variations in temperature and drying time. This study used a completely randomized design (CRD) with two factors: temperature and drying time, each of which was repeated three times. Eucheuma spinosum was extracted using the microwave-assisted extraction (MAE) method with 10% KOH solvent in a ratio of 1:10 for 8 minutes. The first factor is the drying temperature, which consists of three levels: 40°C, 50°C, and 60°C. The second factor is the drying time, which also consists of three levels: 24 hours, 27 hours, and 30 hours. The results of the study showed that (1) temperature and drying time affect the quality characteristics of carrageenan from Eucheuma spinosum dried using the oven method, (2) the parameters affected include water content, ash content, sulfate content, viscosity, and gel strength of carrageenan, and (3) the higher the temperature and duration of drying, the more the water content, ash, protein, and crude fiber in the product tend to decrease. This decrease is in line with the viscosity and gel strength of the resulting carrageenan.